Molecular Detection of Type VI secretion genes and correlation with of IL-10 levels in Pateints with Pantoeaagglomerans - Zahraa T. Wahid,; Layla S. Abdul-Hassan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The present study aimed to detect the presence of HCP and VgrG genes in isolates of Pantoeaagglomerans from infected individuals and to evaluate IL-10 levels as a marker of the immune response activity and its relation with those genes among the participating individuals.Five hospitals in Karbala provided a total of 300 patients varying in age and including both genders for this study. Five milliliters of blood were collected for immunological and molecular testing. The identification of Pantoea species was performed by the VITEK-2 compact system and sequencing analysis. Genomic DNA from bacterial cells was extracted for PCR analysis of specific genes (Hcp and VgrG) to confirm the identity of bacteria and virulence factors. DNA concentration and purity were determined with a Nanodrop spectrophotometer. The PCR process was optimized, and IL-10 was quantified by use of an ELISA kit.In this study on 300 clinical specimens, 79.33% exhibited positive bacterial growth, with 37 of these being Pantoea species. Among the Pantoea isolates, 81.09% were identified as P.agglomerans. The isolates were characterized for their biochemistry and carbohydrate fermentation abilities. Genetic analysis showed that 53.3% of P.agglomerans isolates had the Hcp gene and only 23.3% had the VgrG gene, showing variation in virulence factors.Biofilm production was varied among the isolates; most exhibited strong or moderate biofilm-forming abilities. Patients infected with P.agglomerans also exhibited higher IL-10 levels. Conclusion: The Hcp and VgrG genes of P. agglomerans are involved in immunomodulation. Strong biofilm generation also raises the risk of infection in healthcare environments. Nonetheless, individuals with increased IL-10 levels demonstrate immunomodulation.